Work satisfaction factors: an indicator of human resources in Nursing (Research, Society and Development, 2020)
Objective: to evaluate job satisfaction among nurses at a university hospital in the North of Brazil. Method: descriptive and exploratory study, with quantitative analysis. For data collection, a questionnaire was used to characterize the population and the Professional Satisfaction Index instrument considering the components of autonomy, interaction, professional status, work requirements, organizational norms and remuneration. The data were analyzed using the Statistics Predictive Analytics Software statistical program. Results: 84 nurses participated in the research, mostly female (n = 52, 61.9%), single (n = 43, 51.2%), with postgraduate studies (n = 72, 85.7%). The component that had the most importance was remuneration, with a weighting coefficient of 3.5860 and the least important was professional status with a weighting coefficient of 1.4819. The real level of satisfaction was the remuneration, followed by the components, work requirements, interaction, autonomy, organizational norms and finally the professional status. Conclusion: the level of job satisfaction of nurses at a university hospital in the Northern Region of Brazil was considered low (10.01). The remuneration component was identified as the most important and also as the highest true level of satisfaction.